Power-loss breakdown of a 750-V 100-kW 20-kHz bidirectional isolated DC-DC converter using SiC-MOSFET/SBD dual modules - Akagi H.; Yamagishi T.; Tan N.M.L.; Miyazaki Y.; Kinouchi S.-I.; Koyama M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Conversion efficiency; HVDC power transmission; MOSFET devices; Silicon carbide; Bidirectional isolated dc-dc converter; Conduction loss; Control circuits; Dual active bridges; Gate drives; Power-losses; SiC MOSFET; Switching loss; DC-DC converters